2012
DOI: 10.1101/gad.194266.112
|View full text |Cite
|
Sign up to set email alerts
|

Spatially and genetically distinct control of seed germination by phytochromes A and B

Abstract: Phytochromes phyB and phyA mediate a remarkable developmental switch whereby, early upon seed imbibition, canopy light prevents phyB-dependent germination, whereas later on, it stimulates phyA-dependent germination. Using a seed coat bedding assay where the growth of dissected embryos is monitored under the influence of dissected endosperm, allowing combinatorial use of mutant embryos and endosperm, we show that canopy light specifically inactivates phyB activity in the endosperm to override phyA-dependent sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
147
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(157 citation statements)
references
References 36 publications
(85 reference statements)
9
147
1
Order By: Relevance
“…Moreover, abscisic acid (ABA) signaling interferes with phyA-dependent seed germination (Lee et al, 2012). On the other hand, phyA synergistically coordinates with ABA to inhibit root elongation under white light (Jiang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, abscisic acid (ABA) signaling interferes with phyA-dependent seed germination (Lee et al, 2012). On the other hand, phyA synergistically coordinates with ABA to inhibit root elongation under white light (Jiang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…During the initial phase of seed imbibition, the protein level of phyA is very low, therefore, seed germination is dependent on the red light activation of phyB (phyB-dependent germination) (Shinomura et al, 1994;Seo et al, 2009). After prolonged incubation in the dark (e.g., 48 h), phyA accumulates to high levels and mediates canopy light (FR) induced-seed germination, promoting germination to very low fluence response and FR high irradiation response (Shinomura et al, 1996;Kneissl et al, 2009;Seo et al, 2009;Lee et al, 2012). Recent study showed that canopy light suppresses phyB-dependent germination in the endosperm and activates phyA-dependent germination in the embryo, which involves spatial abscisic acid (ABA) signaling responses (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Upon red light irradiation, the Pr form of phytochrome is converted to the Pfr form to initiate red lightregulated plant development (Quail, 2002;Chen et al, 2004). PhyA and phyB are the main receptors of light-induced seed germination and other PHYs (phyC to E) also play minor roles during the process (Lee et al, 2012). PhyA mediates far-red light (FR), whereas PhyB mediates red light (R)-induced seed germination processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, light plays a major role in initiating seed germination (1-4). Plants perceive light signals through distinct families of photoreceptors, in which the red light photoreceptor phytochrome B (phyB) mediates the initial phase of light-induced seed germination (3,(5)(6)(7)(8). Previous studies showed that in seeds, phyB modulates downstream regulatory networks through one of its interacting factors, phytochrome interacting factor 1 (PIF1) (9-11).…”
mentioning
confidence: 99%